PENERAPAN STRATEGI MENULIS TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN MENGARANG DESKRIPSI SISWA KELAS V SDN 38 PEKANBARU - Cici Oktari; Otang Kurniaman; Lazim N. (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by the low skill of writing descriptions of 5th-grade students of SD Negeri 38 Pekanbaru with 37 students. It is known that no highly skilled students, 5 skilled students, 9 students are quite skilled and 23 students are less skilled in writing descriptions. This type of research is classroom action research conducted in two cycles, each cycle consisting of two meetings and one daily test. This study aims to improve the skills of writing student descriptions. The data in this study were obtained through observation and tests. The data analysis technique used is the analysis of teacher and student activities as well as analysis of skills in writing descriptions. The results of the analysis of teacher activities in the cycle I of the first meeting with a percentage of 75% and the second meeting 79%, while in the cycle II the first meeting with a percentage of 83% and the second meeting 88%. Activities of students in the first cycle I the first meeting with a percentage of 71% and the second meeting 75%, while in the cycle II the first meeting was 79% and the second meeting 83%. The results of the analysis of the skills of writing student descriptions can be seen from before the action carried out the average value of students obtained at 49.51, after the action in the cycle I increased to 75.11 and the cycle II increased to 81.65. From the results of this study it can be concluded that the application of guided writing strategies can improve the skills of writing descriptions of 5th-grade students of SD Negeri 38 Pekanbaru.